Mitochondrial phylogeny and genetic diversity of Hampala barb (Hampala macrolepidota) from the Brantas River, Indonesia - ELOK AMALIA; IFA SUFAICHUSAN; MUHAMMAD DAILAMI; ABD RAHEM FAQIH; MAHENO SRI WIDODO; DEWA GEDE RAKA WIADNYA; WAHYU ENDRA KUSUMA (Society for Indonesian Biodiversity, 2025)
Abstract. Amalia E, Sufaichusan I, Dailami M, Faqih AR, Widodo MS, Wiadnya DGR, Kusuma WE. 2025. Mitochondrial phylogeny and genetic diversity of Hampala barb (Hampala macrolepidota) from the Brantas River, Indonesia. Biodiversitas 26: 5694-5702. Hampala barb (Hampala macrolepidota), a native freshwater fish species in the Brantas River, East Java, is currently under severe threat due to intense fishing and environmental perturbations. The urgency of this situation necessitates the immediate implementation of effective genetic management and conservation programs, which rely on basic scientific information such as genetic characterization. This study aimed to assess the phylogenetic relationships, genetic diversity, population structure, and demographic history of H. macrolepidota using a 1,095 bp sequence of the mitochondrial DNA cytochrome b from 23 individuals collected across four sampling locations. Phylogenetic analysis showed that H. macrolepidota from the Brantas River clustered together and formed a single group with very shallow genetic divergence. Population structure analyses (both ?st and AMOVA) showed high gene flow and an absence of significant genetic clustering, suggesting the sampled area constitutes a single, interconnected population unit. The combination of high haplotype diversity (hd: 0.714-1.000) but low nucleotide diversity (?: 0.00156-0.00728), along with the negative Tajima’s D and Fu’s Fs values, suggested that the species has likely experienced a bottleneck effect followed by a rapid expansion in the past. This decline of genetic diversity points to a reduced long-term adaptive potential, causing the species to be highly vulnerable to future environmental changes, despite its current abundance. The results highlight the urgent need for effective genetic management and conservation programs for the species to focus on maintaining genetic connectivity and minimizing anthropogenic pressures to preserve the genetic integrity and long-term viability of the population. Future studies incorporating nuclear or genome-wide markers would provide finer resolution of population structure and complement the mitochondrial data presented here.